Origins, Development, and Compartmentation of the Granule Cells of the Cerebellum - Consalez, G. Giacomo; Goldowitz, Daniel; Casoni, Filippo; Hawkes, Richard (Frontiers in Neural Circuits, 2021)
Granule cells are the most numerous cell type in the cerebellum and indeed, in the brain: at least 99% of all cerebellar neurons are granule cells. In this review we first consider the formation of the upper rhombic lip, from which all granule cell precursors arise and the way by which the upper rhombic lip generates the external granular layer, a secondary germinal epithelium that serves to amplify the upper rhombic lip precursors. Next we review the mechanisms by which postmitotic granule cells are generated in the external granular layer and migrate radially to settle in the granular layer. In addition, we review the evidence that far from being a homogeneous population, granule cells come in multiple phenotypes with distinct topographical distributions, and consider ways in which this heterogeneity might arise during development.